The development of accounting and application of IFRS in the Czech Republic - Irena Jindrichovska; Dana Kubickova; Sarka Kocmanova (Journal of Accounting and Management Information Systems (JAMIS), 2014)
This paper focuses on development of rules and practices of accounting and on the application of IFRS in the Czech Republic. The article deals with historical background of the Czech accounting and subsequently with particular features of implementation of IFRS after 1989, when the economic transformation to market economy required adjustments in accounting regulation. This part of our research investigates the relationships between local and global standards of accounting, as well as the impact and consequences and perceived benefits of adopting IFRS in accounting practices. In the recent years one can observe some activity to transformation to IFRS in the field of accounting; this however is not systematic or homogenous, as application of local rules is still required in the domain of taxation. Our analysis of development of accounting regulations in the Czech Republic implies that the majority of Czech, companies nowadays have little motivation to switch to international reporting standards especially if there is no further reason for doing so like government requirement, presence of the subject on capital markets or strong business partner - e.g. mother company from abroad the Czech entity to report with the use international format. As to our knowledge, neither the Czech Ministry of Finance nor any other state authority prepares any regulation that would put this international regulation in force unanimously for all public companies.
Keywords: M20; M40; G32; 650; Czech Republic; development of accounting; central management; transformation; IFRS